Moodboards and the Atlas Mnemosyne: possible methodological approaches (Revista de Ensino em Artes, Moda e Design, 2025)
While developing a design project, the moodboard is presented as a creative tool for visual inspiration, which enables the translation of ideas and concepts through images. However, there are only a few specific studies on its methodology and construction. In the field of art history, Aby Warburg (1866-1929) investigated a wide range of documentation and gathered more than a thousand images organized into visual panels in his work Atlas Mnemosyne (1929). The article starts from the hypothesis that it is possible to approximate moodboards to the plates of the Bilderatlas. A methodological approach between design and art history is proposed, and for this purpose, semantic panels and warburgian plates were presented, compared, differentiated, and approximated. As a result of this analysis, it was observed that different imagery sources, including primary sources such as images produced by the designer himself, as well as reproductions of works accessed from museum and collections archives, contribute to richer and more meaningful results. Another aspect revealed concerns the intentionality in organizing the images on the panel, which promotes multiple possibilities for interpretation. Finally, it is suggested that the panel should not be part of just one stage of the design creation process, but rather that it should be revisited at various stages of product development.
Keywords: design; art history; moodboards; Aby Warburg; atlas mnemosyne